Development of rootstocks grapevine and cold stratification time - Junior, Adilson Pimentel [UNESP]; Neto, Francisco José Domingues [UNESP]; da Silva, Marlon Jocimar Rodrigues [UNESP]; Paiva, Ana Paula Maia [UNESP]; Vedoato, Bruna Thais Ferracioli [UNESP]; Simonetti, Lilian Massaro [UNESP]; Tecchio, Marco Antonio [UNESP] (Southern Cross Publishing, 2018)
With the growth of new areas of grapevine planting in Brazil and other tropical countries, the rootstocks play an important role in the implantation of new areas and adaptation of cultivars. The development of new materials has increased productivity per area and even the final quality of the grapes. One of the problems in the propagation of rootstocks grapevine is the natural dormancy present in several species. We aimed to assess the stratification time's initial development and feasibility of grapevines rootstocks stem cuttings on field conditions. Two experiments were carried out. In the experiment of initial development of rootstocks grapevine, were used varieties: 'IAC 572', 'IAC 766', 'IAC 571-6', 'IAC 313', '420-A', 'Vitis Cinerea', 'Riparia de Traviú', 'Rupestris du Lot', 'Kober 5BB', 'SO4', '8B', 'RR101-14', '99R', 'Schwartzmann' and 'Freedom'. In the experiment of stratification time feasibility of grapevines rootstock the varieties used were: 'IAC 572', 'IAC 766', 'IAC 571-6' and 'IAC 313'. In both experiments we assessed the stem cuttings' rooting, sprouting and roots and shoot development. Both experiments, we performed them in a randomized block experimental design, with four replications, ten stems per experimental plot, having in between these cuttings spaces of 12 x 4 cm. During the first experiment, the treatments consisted of 15 rootstock cultivars, and during the second experiment, we used a 4 x 3 factorial scheme, represented by 4 rootstocks and 3 stratification times. The variables we assessed were: percentage of rooted and sprouted cuttings, the branch's and root's length, number of leaves and branches, the roots' and total aerial dry mass. Among the assessed rootstocks in first experiment, the IACs rootstocks presented greater shoot vigor and the 'Riparia de Traviú' increased root system development during field settling. In the second experiment, the 'IAC 572' rootstock presented the best field development rates after stratification. The stem cuttings presented greater vigor when stratified cold during 20 days.
Keywords: Propagation; Root development; Rootstocks; Vigor; Vitis spp